Women Trailblazers in the Law: The New Zealand Women Judges Oral Histories Project - Chan, Elizabeth (Victoria University of Wellington Law Review, 2016)
The New Zealand Women Judges Oral Histories Project aims to provide the first national, publicly accessible records of the lives and careers of trailblazing women judges. As part of this project, this article shares the stories of nine women judges who have broken gender barriers at every stage of their legal studies and careers, including as the first women law graduates, partners of law firms, Queen’s Counsel and judges. In sharing the challenges faced by, and celebrating the successes of, these women judges, their individual stories give context to the statistics showing that women’s participation at the highest levels of the legal profession remains the exception rather than the norm. It is hoped that the achievements of the women who have gone before will inspire today’s young women to reach positions of leadership in the profession, and, more broadly, to strive for equality in both their personal and professional lives.